Preparation method and application of lithium negative electrode based on benzothiazolyl covalent organic framework modification
By using a technology based on benzothiazolyl-based covalent organic frame material modification on the negative electrode of the lithium metal battery, the problems of irregular lithium deposition and dendrite generation during the cycle charging and discharge of lithium metal batteries are solved, and the stability of the battery is achieved and significantly improved security.
Patent Information
- Application Number
- CN202411819251.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Lithium metal batteries are prone to irregular lithium deposition and sharp dendrites during cyclic charging and discharging, resulting in a decrease in battery charging and discharging stability and an increase in safety risks.
Using the preparation method of lithium negative electrode modified based on benzothiazolyl covalent organic frame material, a material with regular group arrangement and nanowire morphology is formed through high-temperature and high-pressure polymerization, and self-assembled into a dense thin protective layer to guide lithium metal Regular deposition and inhibit dendrites.
It significantly improves the charging and discharge stability and safety of lithium metal batteries, extends the cycle life of the battery, and improves the overall performance of the battery without sacrificing ion conduction performance.
Smart Images

Figure CN119431703A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of synthesis and application of functional polymer materials in the energy storage direction, and in particular to a preparation method and application of a lithium negative electrode based on a benzothiazolyl covalent organic framework modification. Background Art
[0002] Under the background of global energy conservation and emission reduction, electrochemical energy storage devices represented by high-performance lithium batteries have great development prospects in the development and wide application of new energy. Lithium metal batteries are considered to be the ultimate solution for high-energy-density power batteries. They have advantages such as high energy density and low electrochemical potential, which makes them have wide application potential in fields such as new energy vehicles. However, corresponding to the urgent demand for practical application is the serious development bottleneck of lithium metal batteries. Among them, the most significant is the battery charging and discharging stability and safety problems caused by lithium dendrites. During the cyclic charging and discharging process of lithium metal batteries, irregular deposition of lithium metal on the negative electrode side will produce more serious accumulation of "dead lithium", resulting in a significant decrease in the battery charging and discharging stability. At the same time, the sharp lithium dendrites produced may pierce the diaphragm or solid electrolyte membrane, causing battery short circuit and serious safety problems.
[0003] In order to overcome the above challenges, the optimization strategy on the electrolyte or electrolyte / electrode interface side can be used to inhibit the formation of dendrites. Among them, lithium metal negative electrode protection has received more attention because it can simultaneously regulate the lithium deposition behavior through active and passive strategies, which has a more significant effect. In terms of active strategy, the nucleation process of lithium ion deposition is regulated by the interaction between the specific groups and structures of the negative electrode protection layer and lithium ions, thereby guiding the regular deposition of lithium metal; in terms of passive strategy, the dense negative electrode protection layer with high mechanical strength can exert pressure from a physical level to resist dendrite growth and significantly reduce the probability of short circuit. However, traditional negative electrode protection materials have significant disadvantages such as difficulty in precise control of structure and composition, low compatibility with lithium metal, and difficulty in self-supporting film formation. The lithium metal negative electrode is often accompanied by more significant volume expansion and contraction during repeated deposition / stripping. How to improve the long-cycle stability of the lithium metal negative electrode protection layer without affecting the ion conductivity performance will become the research focus of the future development and application of lithium metal. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a lithium negative electrode based on benzothiazolyl covalent organic frameworks (COF) and its application.
[0005] The technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a benzothiazole-based covalent organic framework material for lithium negative electrode modification, which is a covalent organic framework material having a benzothiazole group.
[0006] As a further configuration, it is a covalent organic framework material formed by polymerization of benzobisthiazolyl structural monomers and aldehyde structural monomers.
[0007] As a further configuration, the molar ratio of the benzobisthiazolyl structural monomer to the aldehyde structural monomer is (1-2):1.
[0008] As a further configuration, the polymerization conditions are as follows: dissolving the benzobisthiazolyl structural monomer and the aldehyde structural monomer in a system comprising solvent A, solvent B, and catalyst A, and performing high pressure polymerization reaction at 150-200° C. for 60-85 hours.
[0009] As a further configuration, the solvent A includes one or more of o-dichlorobenzene, p-dichlorobenzene, and mesitylene; the solvent B includes one or more of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the catalyst A includes one or more of trifluoromethanesulfonic acid, scandium trifluoromethanesulfonate, aluminum trifluoromethanesulfonate, zinc trifluoromethanesulfonate, and lithium trifluoromethanesulfonate.
[0010] As a further setting, the temperature of the high temperature and high pressure polymerization is set to 150-200° C., and the time is set to 60-85 h.
[0011] As a further setting, the high temperature and high pressure polymerization reaction is carried out in a thick-walled pressure-resistant tube, and argon gas is first blown to remove the air in the tube before the polymerization reaction.
[0012] As a further configuration, the aldehyde structural monomer is selected from at least one of 1,3,5-tri(4-formylphenyl)triazine, 1,3,5-tri(4-formylphenyl)benzene, triformylphenylamine, 1,3,5-tri(3-formylphenyl)benzene, 1,3,5-triformylbenzene, and 1,3,5-triformyl-2,4,6-trimethylbenzene.
[0013] As a further configuration, the benzobisthiazolyl structural monomer is specifically 2,6-dimethylbenzene [1,2-d:4,5-d'] bis (thiazole) (DBBT), and the preparation method thereof is as follows:
[0014] 2,5-diamino-1,4-dithiophenol dihydrochloride is suspended and dispersed in solvent D and an acid-binding agent is added dropwise to obtain a dispersion. The dispersion is added to a certain amount of a mixed system of triethyl orthoacetate and a catalyst through a syringe, stirred at a specific temperature, and then cooled and diluted. The crude reaction product is obtained by filtration and recrystallized using a specific purification solvent to obtain a white needle-shaped monomer 2,6-dimethylbenzene [1,2-d:4,5-d'] bis (thiazole) (DBBT).
[0015] The solvent D is selected from one or more of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the acid binding agent is selected from one or more of pyridine, triethylamine, and potassium carbonate; the stirring temperature is controlled within the range of 30-80 degrees, and the stirring time is 1-2 hours; the purification solvent is selected from one or more of dichloromethane, chloroform, n-hexane, cyclohexane, ether, and tetrahydrofuran.
[0016] The second aspect of the present invention provides a method for preparing a lithium negative electrode modified by a benzothiazolyl covalent organic framework material, the steps of which are as follows:
[0017] (1) adding the benzothiazolyl covalent organic framework material prepared as above, a binder and a lithium salt into a solvent C and dispersing them to obtain a dispersion;
[0018] (2) applying the dispersion obtained in step (1) to the surface of lithium metal to form a film, and drying the lithium metal coated with the dispersion wet film to obtain a lithium negative electrode modified with a benzothiazole-based covalent organic framework material.
[0019] As a further configuration, in step (1), the binder is selected from one or more of polyvinylidene fluoride, polyethylene oxide, and poly(vinylidene fluoride-hexafluoropropylene),
[0020] The lithium salt is selected from one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), and lithium trifluoromethanesulfonyl imide.
[0021] As a further configuration, the mass ratio of the benzothiazolyl covalent organic framework material, the binder, and the lithium salt is 65-85:0-10:10-25.
[0022] The third aspect of the present invention provides an application of a lithium negative electrode modified with a benzothiazolyl-based covalent organic framework material prepared by the above method in the field of lithium-ion batteries.
[0023] The beneficial effects of the present invention are as follows:
[0024] 1. The present invention combines the polymerization process to prepare a highly regular benzothiazole-based covalent organic framework material under relatively mild conditions. The material has a special nanowire morphology and regular group arrangement, and can self-assemble on the surface of lithium metal under low / no binder conditions to form a dense thin protective layer. The inherent amino and benzothiazole groups in its skeleton structure can effectively promote the dissociation of lithium salts and guide the regular deposition of lithium metal. Matching the lithium symmetry and full battery system can achieve a significant improvement in its charge and discharge stability without sacrificing the system's ion conductivity performance.
[0025] 2. The polar benzobithiazole groups inside the COF material molecules of the present invention can promote the dissociation of lithium salts, and the ordered porous structure can provide uniform ion transmission channels, thereby guiding lithium ions to deposit uniformly on the surface of lithium metal and reducing dendrite growth. The rigid structure of the COF material can provide mechanical support to resist the volume expansion of lithium metal during the charge and discharge process. The excellent electronic insulation and ion conductivity of the COF material can participate in the construction of the artificial SEI layer, avoiding the influence of electrons directly passing through the electrolyte on its stability and reducing the occurrence of electrochemical side reactions.
[0026] 3. Different from the commonly used groups in the construction of traditional covalent organic framework materials, the benzothiazole group has a more rigid planar molecular configuration. Assembling it into a two-dimensional covalent organic framework is conducive to the orderly arrangement of molecules, and then a more continuous lithium-conducting channel can be constructed at the electrode / electrolyte interface, guiding the uniform deposition of lithium ions and promoting efficient lithium conduction. In addition, the benzothiazole group is rich in S and N atoms, which can reversibly coordinate Li ions through controlled ion complexation and release, and set binding sites on the inner wall of the continuous lithium-conducting channel to achieve synergistic lithium conduction. Third, this ordered intermolecular stacking formed by the π-π interaction of the benzothiazole conjugated system has stronger self-assembly mechanical properties, which has a significant effect on inhibiting the formation of lithium dendrites.
[0027] 4. The benzothiazolyl-based covalent organic framework material prepared by the method provided by the present invention has a simple preparation process and high yield, and is matched with a scraping coating process, which can effectively solve the major bottleneck of lithium metal battery stability. The improved lithium metal symmetric battery matched with a polyethylene oxide all-solid electrolyte can achieve continuous and stable lithium insertion and extraction for more than 600 hours at a current density of 0.2 mA / cm2, and has broad application prospects in the development of high-safety and high-energy-density lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0029] Figure 1 is the chemical reaction formula of each embodiment of the present invention;
[0030] Figure 2 Solid-state NMR carbon spectroscopy characterization of some benzothiazolyl-based COF materials;
[0031] Figure 3 TEM characterization of some benzothiazolyl-based COF materials;
[0032] Figure 4 The figure shows a comparison of the cycling performance of lithium metal symmetric batteries of some embodiments and comparative examples. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0034] Example 1
[0035] Step S1, 2,5-diamino-1,4-dithiophenol dihydrochloride (1.47 g, 6.0 mmol) was suspended and dispersed in 12 mL of dimethylacetamide, and 12.5 mmol of pyridine was added dropwise to obtain dispersion A; dispersion A was added to a mixed system of 18.0 mmol of triethyl orthoacetate and 0.3 mmol of scandium trifluoromethanesulfonate through a syringe, stirred at 50°C for 1.5 hours, then cooled to room temperature and diluted with water. The crude reaction product was obtained by filtration and recrystallized with a mixed solvent of dichloromethane and n-hexane to obtain a white needle-shaped monomer 2,6-dimethylbenzene [1,2-d:4,5-d'] bis (thiazole) (DBBT).
[0036] Step S2: Pre-bubble argon gas into a thick-walled pressure tube for 5 minutes to remove air, add 0.3 mmol DBBT, 0.2 mmol 1,3,5-tris(4-formylphenyl)triazine, 7 mL dimethylformamide, 3 mL o-dichlorobenzene, and 2 mL trifluoromethanesulfonic acid into the pressure tube, and perform ultrasound for ten minutes to fully disperse the product. Heat the reaction tube to 180°C in a closed state for three days. After the reaction, cool the mixture to room temperature and use 0.1 mol L -1 The precipitated product was collected and washed with methanol, tetrahydrofuran and dichloromethane (50 mL of each solvent each time, repeated three times). The washed product was dried under vacuum at 60°C for 12 hours to obtain yellow COF-1 powder.
[0037] Step S3, dissolving and dispersing 85 mg COF-1 powder, 5 mg polyvinylidene fluoride, and 10 mg lithium bis(trifluoromethanesulfonyl)imide in 3 mL anhydrous N-methylpyrrolidone to obtain a slurry, and evenly scraping the slurry on the surface of lithium metal to control the wet film thickness to 300 μm.
[0038] The lithium metal coated with the slurry wet film is dried at room temperature and then vacuum dried at 80 degrees overnight to finally obtain the surface-protected lithium metal negative electrode.
[0039] Example 2
[0040] The difference between this embodiment and embodiment 1 is that in step S3, 75 mg of COF-1 powder, 5 mg of polyvinylidene fluoride, and 20 mg of lithium bis(trifluoromethanesulfonyl)imide are dissolved and dispersed in 3 mL of anhydrous acetone to obtain a slurry, and the slurry is evenly scraped on the surface of lithium metal to control the wet film thickness to 300 μm.
[0041] The lithium metal coated with the slurry wet film was dried at room temperature and then vacuum dried at 60 degrees overnight to finally obtain the surface-protected lithium metal negative electrode.
[0042] Example 3
[0043] The difference between this embodiment and embodiment 1 is that in step S2, 1,3,5-tri(4-formylphenyl)benzene is used instead of 1,3,5-tri(4-formylphenyl)triazine, and the remaining processes and process parameters are the same to prepare COF-2 powder. In step S3, COF-2 powder is used instead of COF-1 powder.
[0044] Example 4
[0045] The difference between this embodiment and embodiment 1 is that in step S2, triformylphenylamine is used instead of 1,3,5-tri(4-formylphenyl)triazine, and the remaining processes and process parameters are the same and will not be repeated here. COF-3 powder is prepared, and in step S3, COF-3 powder is used instead of COF-1 powder.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 1 is that in step S2, 1,3,5-tri(3-formylphenyl)benzene is used instead of 1,3,5-tri(4-formylphenyl)triazine, and the remaining processes and process parameters are the same and will not be repeated here. COF-4 powder is prepared, and in step S3, COF-4 powder is used instead of COF-1 powder.
[0048] Example 6
[0049] The difference between this embodiment and embodiment 1 is that in step S2, 1,3,5-tri(3-formylphenyl)benzene is used instead of 1,3,5-tri(4-formylphenyl)triazine, and the remaining processes and process parameters are the same and will not be repeated here. COF-5 powder is prepared, and in step S3, COF-5 powder is used instead of COF-1 powder.
[0050] Example 7
[0051] The difference between this embodiment and embodiment 1 is that in step S2, 1,3,5-triformyl-2,4,6-trimethylbenzene is used instead of 1,3,5-tri(4-formylphenyl)triazine, and the remaining processes and process parameters are the same and will not be repeated here. COF-6 powder is prepared, and in step S3, COF-6 powder is used instead of COF-1 powder.
[0052] Example 8
[0053] The difference between this embodiment and embodiment 3 is that in step S3, 80 mg of COF-2 powder and 20 mg of lithium bis(trifluoromethanesulfonyl)imide are dissolved and dispersed in 3 mL of anhydrous acetone to obtain a slurry, and the slurry is evenly scraped on the surface of lithium metal to control the wet film thickness to 300 μm.
[0054] Example 9
[0055] The difference between this embodiment and embodiment 3 is that in step S3, 75 mg of COF-2 powder, 5 mg of poly(vinylidene fluoride-hexafluoropropylene), and 20 mg of lithium bis(trifluoromethanesulfonyl imide) are dissolved and dispersed in 3 mL of anhydrous acetone to obtain a slurry, and the slurry is evenly scraped on the surface of lithium metal to control the wet film thickness to 300 μm.
[0056] The lithium metal coated with the slurry wet film was dried at room temperature and then vacuum dried at 60 degrees overnight to finally obtain the surface-protected lithium metal negative electrode.
[0057] Example 10
[0058] The difference between this embodiment and embodiment 4 is that in step S3, 75 mg of COF-3 powder, 5 mg of polyvinylidene fluoride, and 20 mg of lithium bis(trifluoromethanesulfonyl)imide are dissolved and dispersed in 3 mL of anhydrous acetone to obtain a slurry, and the slurry is evenly scraped on the surface of lithium metal to control the wet film thickness to 300 μm.
[0059] The lithium metal coated with the slurry wet film was dried at room temperature and then vacuum dried at 60 degrees overnight to finally obtain the surface-protected lithium metal negative electrode.
[0060] Comparative Example 1
[0061] In this comparative example, an unmodified lithium sheet without surface protection is selected as the lithium metal negative electrode.
[0062] Comparative Example 2
[0063] 33 mg of polyvinylidene fluoride and 66 mg of lithium bis(trifluoromethanesulfonyl)imide were dispersed in 3 mL of anhydrous N-methylpyrrolidone to obtain a slurry, and the slurry was evenly scraped on the surface of lithium metal to control the wet film thickness to 300 μm.
[0064] The lithium metal coated with the slurry wet film is dried at room temperature and then vacuum dried at 80 degrees overnight to finally obtain the surface-protected lithium metal negative electrode.
[0065] Comparative Example 3
[0066] 100 mg of polyvinylidene fluoride was dispersed in 3 mL of anhydrous N-methylpyrrolidone to obtain a slurry, and the slurry was evenly scraped on the surface of lithium metal to control the wet film thickness to 300 μm.
[0067] The lithium metal coated with the slurry wet film is dried at room temperature and then vacuum dried at 80 degrees overnight to finally obtain the surface-protected lithium metal negative electrode.
[0068] Liquid NMR hydrogen spectrum was used to analyze the group composition of the synthesized COF. The NMR test results of some examples are as follows: Figure 2 shown.
[0069] The COF samples prepared above were ground and fully ultrasonically dispersed in anhydrous ethanol, and the samples were prepared for TEM characterization. The NMR test results of some samples of the examples are as follows: Figure 3 As shown in the figure, different COF materials show significantly different morphologies, among which COF-1 presents a special nanowire morphology, which gives it great potential for self-supporting film formation.
[0070] The surface protected lithium metal prepared above was matched with a polyethylene oxide-based all-solid polymer electrolyte (electrolyte composition: polyethylene oxide with a number average molecular weight of 1 million, lithium bis(trifluoromethanesulfonyl)imide, the mass ratio of the two being 0.69:0.25, and the film was prepared by acetonitrile solution casting method, with a film thickness of 100 μm), and a Li||Li symmetric battery was assembled and tested for its lithium insertion and extraction cycle performance at 65°C and 0.1 mAh / cm2. The performance of some embodiments and comparative examples is shown in FIG. Figure 4 As shown in Table 1. As can be seen from the figure, the COF material and negative electrode protection process designed in this patent play a significant role in guiding the regular deposition of lithium metal, inhibiting the formation of dendrites, and improving the stability of lithium metal batteries.
[0071] Table 1 Cyclic performance test of Li||Li symmetric battery assembled by preparing all-solid electrolyte membrane in some embodiments and comparative examples
[0072]
[0073] As can be seen from the table, the lithium symmetric battery assembled by combining the benzothiazolyl covalent organic framework synthesized by the present invention with the lithium metal surface coating process shows significantly optimized interface compatibility and long cycle stability compared with the control example, which can be attributed to the excellent lithium deposition guiding effect and dendrite inhibition ability of the COF material.
[0074] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A benzothiazolyl-based covalent organic framework material for lithium anode modification, characterized in that: It is a covalent organic framework material with benzothiazole groups.
2. A benzothiazolyl-based covalent organic framework material for lithium negative electrode modification according to claim 1, characterized in that: It is a covalent organic framework material formed by polymerization of benzobisthiazolyl structural monomers and aldehyde structural monomers.
3. A benzothiazolyl-based covalent organic framework material for lithium negative electrode modification according to claim 2, characterized in that: The molar ratio of the benzobisthiazolyl structural monomer to the aldehyde structural monomer is (1-2):
1.
4. A benzothiazolyl-based covalent organic framework material for lithium negative electrode modification according to claim 2, characterized in that: The polymerization conditions are as follows: dissolving the benzobisthiazolyl structural monomer and the aldehyde structural monomer in a system comprising solvent A, solvent B and catalyst A, and performing high pressure polymerization reaction at 150-200° C. for 60-85 hours.
5. A benzothiazolyl-based covalent organic framework material for lithium negative electrode modification according to claim 4, characterized in that: The solvent A includes one or more of o-dichlorobenzene, p-dichlorobenzene, and mesitylene; the solvent B includes one or more of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; and the catalyst A includes one or more of trifluoromethanesulfonic acid, scandium trifluoromethanesulfonate, aluminum trifluoromethanesulfonate, zinc trifluoromethanesulfonate, and lithium trifluoromethanesulfonate.
6. A benzothiazolyl-based covalent organic framework material for lithium negative electrode modification according to claim 2, characterized in that: The aldehyde structural monomer is selected from at least one of 1,3,5-tris(4-formylphenyl)triazine, 1,3,5-tris(4-formylphenyl)benzene, triformylphenylamine, 1,3,5-tris(3-formylphenyl)benzene, 1,3,5-triformylbenzene, and 1,3,5-triformyl-2,4,6-trimethylbenzene.
7. A method for preparing a lithium negative electrode modified by a benzothiazolyl covalent organic framework material, characterized in that: Here are the steps: (1) adding the benzothiazolyl covalent organic framework material prepared by the method of any one of claims 1 to 6, a binder and a lithium salt into a solvent C and dispersing them to obtain a dispersion; (2) applying the dispersion obtained in step (1) to the surface of lithium metal to form a film, and drying the lithium metal coated with the dispersion wet film to obtain a lithium negative electrode modified with a benzothiazole-based covalent organic framework material.
8. The method for preparing a lithium negative electrode modified by a benzothiazolyl covalent organic framework material according to claim 7, characterized in that: In step (1), the binder is selected from one or more of polyvinylidene fluoride, polyethylene oxide, and poly(vinylidene fluoride-hexafluoropropylene), The lithium salt is selected from one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), and lithium trifluoromethanesulfonyl imide.
9. The method for preparing a lithium negative electrode modified by a benzothiazolyl covalent organic framework material according to claim 7, characterized in that: The mass ratio of the benzothiazolyl covalent organic framework material, the binder and the lithium salt is 65-85:0-10:10-25.
10. Application of a lithium negative electrode modified with a benzothiazolyl covalent organic framework material prepared by the method of any one of claims 7 to 9 in the field of lithium-ion batteries.
Citation Information
Patent Citations
Preparation of benzobithiazolyl covalent organic framework material and applications of benzobithiazolyl covalent organic framework material in supercapacitors
CN110790932A
Thiazolyl sulfur-rich covalent organic framework as well as preparation method and application thereof
CN113336961A
Preparation method and application of lithium negative electrode based on covalent organic framework material modification
CN115403723A
Covalent organic framework material containing multiple oxidation-reduction active groups as well as preparation method and application of covalent organic framework material
CN117700738A
Preparation method of lithium battery negative electrode material based on benzothiadiazole covalent organic framework
CN118983441A